JP3141907B2 - Method for producing spindle-shaped iron-based metal magnetic particle powder - Google Patents

Method for producing spindle-shaped iron-based metal magnetic particle powder

Info

Publication number
JP3141907B2
JP3141907B2 JP05042118A JP4211893A JP3141907B2 JP 3141907 B2 JP3141907 B2 JP 3141907B2 JP 05042118 A JP05042118 A JP 05042118A JP 4211893 A JP4211893 A JP 4211893A JP 3141907 B2 JP3141907 B2 JP 3141907B2
Authority
JP
Japan
Prior art keywords
particles
spindle
compound
particle powder
aqueous
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Expired - Fee Related
Application number
JP05042118A
Other languages
Japanese (ja)
Other versions
JPH06228614A (en
Inventor
晴己 黒川
健二 沖中
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Toda Kogyo Corp
Original Assignee
Toda Kogyo Corp
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Toda Kogyo Corp filed Critical Toda Kogyo Corp
Priority to JP05042118A priority Critical patent/JP3141907B2/en
Publication of JPH06228614A publication Critical patent/JPH06228614A/en
Application granted granted Critical
Publication of JP3141907B2 publication Critical patent/JP3141907B2/en
Anticipated expiration legal-status Critical
Expired - Fee Related legal-status Critical Current

Links

Landscapes

  • Manufacture Of Metal Powder And Suspensions Thereof (AREA)

Description

【発明の詳細な説明】DETAILED DESCRIPTION OF THE INVENTION

【0001】[0001]

【産業上の利用分野】本発明は、粒度が均斉であって樹
枝状粒子が混在しておらず、しかも、高い保磁力を有す
る紡錘状を呈した鉄を主成分とする金属磁性粒子粉末の
製造法に関するものである。
BACKGROUND OF THE INVENTION The present invention relates to a spindle-shaped iron-based metal magnetic particle powder having a uniform particle size, free of dendritic particles, and having a high coercive force. It concerns the manufacturing method.

【0002】[0002]

【従来の技術】近年、VTR(ビデオ・テープ・レコー
ダー)の普及は目覚ましく、長時間記録化並びに小型軽
量化を目指したVTRの開発が盛んに行われていると共
に、これに用いる磁気記録媒体に対する高性能化、高密
度記録化の要求も益々高まってきている。
2. Description of the Related Art In recent years, VTRs (video tape recorders) have been remarkably popularized. VTRs aiming at long-time recording and miniaturization and lightening have been actively developed, and magnetic recording media used in the VTRs have been developed. Demands for higher performance and higher density recording are also increasing.

【0003】即ち、磁気記録媒体の高画像画質、高出力
特性、殊に周波数特性の向上が要求され、その為には、
残留磁束密度Brの向上、高保磁力化及びテープ表面の
平滑性の向上が必要であり、益々S/N比の向上が要求
されてきている。
[0003] That is, the magnetic recording medium is required to have high image quality, high output characteristics, and especially improvement in frequency characteristics.
It is necessary to improve the residual magnetic flux density Br, increase the coercive force, and improve the smoothness of the tape surface, and the S / N ratio is increasingly required.

【0004】周知の通り、磁気記録媒体のこれらの諸特
性は使用される磁性粒子粉末と密接な関係を有してお
り、従来の酸化鉄磁性粒子粉末に比較して高い保磁力と
大きな飽和磁化を有する鉄を主成分とする金属磁性粒子
粉末がディジタルオーディオテープ(DAT)、8mm
ビデオテープ、Hi−8テープ並びにビデオフロッピー
等の磁気記録媒体に使用され実用化されている。しかし
ながら、これらの鉄を主成分とする金属磁性粒子粉末に
ついても更に特性改善が強く望まれている。
As is well known, these characteristics of a magnetic recording medium are closely related to the magnetic particle powder used, and have a higher coercive force and a larger saturation magnetization than conventional iron oxide magnetic particle powder. Metal magnetic particle powder containing iron as a main component is a digital audio tape (DAT), 8 mm
It is used and practically used for magnetic recording media such as video tapes, Hi-8 tapes, and video floppies. However, it is strongly desired to further improve the properties of these metal magnetic particle powders containing iron as a main component.

【0005】即ち、磁気記録媒体の諸特性と使用される
磁性粒子粉末の特性との関係について詳述すれば次の通
りである。
That is, the relationship between the characteristics of the magnetic recording medium and the characteristics of the magnetic particle powder used will be described in detail below.

【0006】ビデオ用磁気記録媒体として高画像画質を
得る為には、日経エレクトロニクス(1976年)5月
3日号第82〜105頁の記載からも明らかな通り、
ビデオS/N比、クロマS/N比、ビデオ周波数特
性の向上が要求される。
In order to obtain high image quality as a magnetic recording medium for video, it is clear from the description of Nikkei Electronics (1976), May 3, page 82-105, that
Improvements in video S / N ratio, chroma S / N ratio, and video frequency characteristics are required.

【0007】ビデオS/N比及びクロマS/N比の向上
をはかる為には、磁性粒子粉末のビヒクル中での分散
性、塗膜中での配向性及び充填性を向上させること、並
びに、磁気記録媒体の表面平滑性を改良することが重要
であり、そのような磁性粒子粉末としては、粒度が均斉
であって、樹枝状粒子が混在しておらず、しかも、軸比
(長軸径/短軸径−以下同じ−)が大きいことが要求さ
れる。
In order to improve the video S / N ratio and the chroma S / N ratio, it is necessary to improve the dispersibility of the magnetic particle powder in a vehicle, the orientation and the filling property in a coating film, and It is important to improve the surface smoothness of a magnetic recording medium. Such magnetic particles have a uniform particle size, do not contain dendritic particles, and have an axial ratio (long axis diameter). / Small shaft diameter-the same applies hereinafter) is required to be large.

【0008】次に、ビデオ周波数特性の向上を図る為に
は、磁気記録媒体の保磁力Hcが高く、且つ、残留磁束
密度Brが大きいことが必要である。磁気記録媒体の保
磁力Hcを高める為には、磁性粒子粉末の保磁力Hcが
できるだけ高いことが要求されており、現在、ビデオフ
ロッピー用、DAT用、8mmビデオ用、Hi−8用に
使用される磁性粒子粉末の保磁力は、1300Oe〜1
800Oe程度が要求されている。これに用いる磁性粒
子粉末の保磁力は、一般にはその形状異方性に起因して
生じるので粒子の軸比が大きくなる程保磁力は増加する
傾向にある。
Next, in order to improve the video frequency characteristics, it is necessary that the coercive force Hc of the magnetic recording medium be high and the residual magnetic flux density Br be large. In order to increase the coercive force Hc of the magnetic recording medium, it is required that the coercive force Hc of the magnetic particle powder be as high as possible, and is currently used for video floppy, DAT, 8 mm video, and Hi-8. The coercive force of the magnetic particles is 1300 Oe to 1
About 800 Oe is required. The coercive force of the magnetic particle powder used for this purpose generally occurs due to its shape anisotropy. Therefore, the coercive force tends to increase as the axial ratio of the particles increases.

【0009】鉄を主成分とする磁性粒子粉末は、一般
に、出発原料であるゲータイト粒子、これを加熱脱水し
て得られるヘマタイト粒子、又はこれらに鉄以外の異種
金属を含有する粒子を還元性ガス中、加熱還元すること
により得られている。
The magnetic particle powder containing iron as a main component is generally prepared by reducing goethite particles as a starting material, hematite particles obtained by heating and dehydrating the particles, or particles containing a different metal other than iron in a reducing gas. Medium, obtained by heat reduction.

【0010】上述した通り、粒度が均斉であって樹枝状
粒子が混在しておらず、しかも、高い保磁力を有する鉄
を主成分とする磁性金属粒子粉末は、現在、最も要求さ
れているところであり、このような特性を備えた鉄を主
成分とする磁性金属粒子粉末を得るためには、出発原料
であるゲータイト粒子粉末の粒度が均斉であって樹枝状
粒子が混在しておらず、しかも、大きな軸比を有するこ
とが要求される。
As described above, magnetic metal particles mainly composed of iron and having a high coercive force and having a uniform particle size and no dendritic particles are presently required at the present time. In order to obtain magnetic metal particle powder containing iron as a main component having such characteristics, the particle size of the goethite particle powder as a starting material is uniform and dendritic particles are not mixed, and , It is required to have a large axial ratio.

【0011】従来、出発原料であるゲータイト粒子粉末
を製造する方法としては、第一鉄塩水溶液に当量以上
の水酸化アルカリ水溶液を加えて得られる水酸化第一鉄
コロイドを含む懸濁液をpH11以上にて80℃以下の
温度で酸素含有ガスを通気して酸化反応を行うことによ
り針状ゲータイト粒子を生成させる方法(例えば、特公
昭39−5610号公報)や第一鉄塩水溶液と炭酸ア
ルカリ水溶液とを反応させて得られたFeCO3 を含む
懸濁液に酸素含有ガスを通気して酸化反応を行うことに
より紡錘状を呈したゲータイト粒子を生成させる方法
(例えば、特開昭50−80999号公報)等が知られ
ている。
Conventionally, as a method for producing goethite particle powder as a starting material, a suspension containing a ferrous hydroxide colloid obtained by adding an equivalent or more of an aqueous alkali hydroxide solution to an aqueous ferrous salt solution is used. As described above, a method of generating needle-like goethite particles by passing an oxygen-containing gas at a temperature of 80 ° C. or lower to perform an oxidation reaction (for example, Japanese Patent Publication No. 39-5610), an aqueous ferrous salt solution and an alkali carbonate A method in which an oxygen-containing gas is passed through a suspension containing FeCO 3 obtained by reacting with an aqueous solution to cause an oxidation reaction, thereby producing spindle-shaped goethite particles (for example, JP-A-50-80999). Is known.

【0012】[0012]

【発明が解決しようとする課題】粒度が均斉であって樹
枝状粒子が混在しておらず、しかも、高い保磁力を有す
る鉄を主成分とする金属磁性粒子粉末は、現在最も要求
されているところであるが、出発原料であるゲータイト
粒子粉末を製造する前出の方法による場合には、軸比
の大きな殊に、10以上の針状ゲータイト粒子が生成す
るが、樹枝状粒子が混在しており、また、粒度から言え
ば、均斉な粒度を有した粒子とは言い難い。
SUMMARY OF THE INVENTION Metal magnetic particle powder containing iron as a main component having a uniform particle size, containing no dendritic particles, and having a high coercive force is the most required at present. By the way, according to the above-mentioned method of producing goethite particle powder as a starting material, needle-like goethite particles having a large axial ratio, particularly 10 or more, are generated, but dendritic particles are mixed. Also, in terms of the particle size, it cannot be said that the particles have a uniform particle size.

【0013】前出の方法による場合には、粒度が均斉
であり、また、樹枝状粒子が混在していない紡錘状を呈
した粒子が生成するが、一方、軸比は高々7程度であ
り、軸比の大きな粒子が生成し難いという欠点があり、
殊に、この現象は生成粒子の長軸径が小さくなる程顕著
になるという傾向にある。
In the case of the above-mentioned method, spindle-shaped particles having a uniform particle size and containing no dendritic particles are produced. On the other hand, the axial ratio is at most about 7; There is a disadvantage that particles with a large axial ratio are difficult to generate,
In particular, this phenomenon tends to become more pronounced as the major axis diameter of the produced particles decreases.

【0014】これらゲータイト粒子粉末を出発原料粒子
として得られた鉄を主成分とする金属磁性粒子粉末もま
た粒度が均斉であって樹枝状粒子が混在しておらず、し
かも、大きな軸比を有しているとは言い難いものであ
る。
[0014] The iron-based metal magnetic particle powder obtained using the goethite particle powder as a starting material particle is also uniform in particle size, does not contain dendritic particles, and has a large axial ratio. It is hard to say that they do.

【0015】一方、ゲータイト粒子中にAl化合物を含
有させることにより、生成したゲータイト粒子を加熱脱
水時または加熱還元時に粒子形状のくずれ及び粒子間の
焼結防止することができると共に、磁気記録媒体とする
際の分散性、充填性、テープ表面の平滑性を向上させる
ことができることが知られており、その先行技術とし
て、例えば、特公平3−43324号公報が挙げられ
る。
On the other hand, by adding an Al compound to the goethite particles, it is possible to prevent the generated goethite particles from being deformed during heat dehydration or heat reduction and to prevent sintering between the particles, and to reduce the magnetic recording medium It is known that the dispersibility, the filling property, and the smoothness of the tape surface can be improved. For example, Japanese Patent Publication No. 43324/1991 is mentioned as the prior art.

【0016】しかし、同公報記載の技術手段である第一
鉄塩水溶液に炭酸ソーダ及び水溶性Al化合物を含む水
溶液を混合し、空気を吹き込んでα−FeOOHを生成
させ、更に該α−FeOOHにSi化合物を被着させる
処理をした後、水素気流中300〜600℃の温度で還
元することを特徴とする金属磁性粉末の製造方法では、
得られる金属磁性粉末の保磁力は700〜1200Oe
程度である。
However, an aqueous solution containing sodium carbonate and a water-soluble Al compound is mixed with an aqueous solution of ferrous salt, which is a technical means described in the publication, and air is blown to generate α-FeOOH. In a method for producing a metal magnetic powder, the method comprising applying a Si compound and then reducing it in a hydrogen stream at a temperature of 300 to 600 ° C.
The coercive force of the obtained metal magnetic powder is 700 to 1200 Oe.
It is about.

【0017】また、添加する水溶性Al化合物について
は、アルミナゾルの場合には、微細かつ軸比の著しく小
さいものしか得られないため、当該ゲータイト粒子を用
いて得られる金属磁性粒子粉末は高い保磁力のものが得
られ難い。アルミン酸ソーダのような塩基性塩化合物の
みを添加した場合には、生成するゲータイト粒子の粒子
が粗大化すると共に軸比の大きなものは得られ難い。ま
た、塩化アルミニウムや硫酸アルミニウムのような酸性
塩化合物のみを添加した場合には、微細化すると共に軸
比の大きなものが得られ難い。
As for the water-soluble Al compound to be added, in the case of alumina sol, only fine particles having an extremely small axial ratio can be obtained. Therefore, the metal magnetic particles obtained by using the goethite particles have a high coercive force. Is difficult to obtain. When only a basic salt compound such as sodium aluminate is added, the resulting goethite particles become coarse and it is difficult to obtain those having a large axial ratio. Further, when only an acidic salt compound such as aluminum chloride or aluminum sulfate is added, it is difficult to obtain a finer one having a large axial ratio.

【0018】そこで、本発明は、粒度が均斉であって樹
枝状粒子が混在しておらず、しかも、Alを含有する紡
錘状を呈したゲータイト粒子粉末を出発原料として生成
することにより、粒度が均斉であって樹枝状粒子が混在
しておらず、しかも、高い保磁力を有する紡錘状を呈し
た鉄を主成分とする金属磁性粒子粉末を得ることを技術
的課題とする。
Accordingly, the present invention provides a goethite particle powder having a uniform particle size, no dendritic particles, and a spindle-like shape containing Al as a starting material. An object of the present invention is to obtain a spindle-shaped iron-based metal magnetic particle powder which is uniform and contains no dendritic particles and has a high coercive force.

【0019】[0019]

【課題を解決するための手段】前記技術的課題は、次の
通りの本発明方法によって達成できる。 即ち、本発明は、第一鉄塩水溶液と炭酸アルカリ水溶液
とを反応して得られたFeCO3 を含む懸濁液に酸素含
有ガスを通気して酸化反応を行うことにより紡錘状を呈
したゲータイト粒子を生成させ、該ゲータイト粒子又は
該ゲータイト粒子を加熱脱水して得られた紡錘状を呈し
たヘマタイト粒子を還元性ガス中で加熱還元する紡錘状
を呈した鉄を主成分とする金属磁性粒子粉末の製造法に
おいて、 あらかじめ、前記第一鉄塩水溶液中にはAlの酸性塩化
合物を、前記炭酸アルカリ水溶液中にはAlの塩基性塩
化合物を、それぞれ添加しておくことからなる紡錘状を
呈した鉄を主成分とする金属磁性粒子粉末の製造法であ
る。
The above technical object can be achieved by the following method of the present invention. That is, the present invention provides a spindle-shaped goethite having an oxygen-containing gas passed through a suspension containing FeCO 3 obtained by reacting an aqueous ferrous salt solution and an aqueous alkali carbonate solution to perform an oxidation reaction. Particles are generated, and the spindle-shaped metal magnetic particles containing iron as a main component are obtained by heating and reducing the goethite particles or the spindle-shaped hematite particles obtained by heating and dehydrating the goethite particles in a reducing gas. In the method for producing a powder, a spindle shape comprising adding an acidic salt compound of Al in the aqueous ferrous salt solution and a basic salt compound of Al in the aqueous alkali carbonate solution in advance is used. This is a method for producing metal magnetic particle powder containing iron as a main component.

【0020】尚、前記第一鉄塩水溶液中に添加するAl
の酸性塩化合物が該第一鉄塩水溶液中のFeに対しAl
換算で1.0〜3.0原子%の範囲であり、前記炭酸ア
ルカリ水溶液中に添加するAlの塩基性塩化合物が前記
第一鉄塩水溶液中のFeに対しAl換算で1.0〜3.
0原子%の範囲であることが望ましい。
In addition, Al added to the ferrous salt aqueous solution
Is an acid salt compound of Al with respect to Fe in the aqueous ferrous salt solution.
It is in the range of 1.0 to 3.0 atomic% in terms of conversion, and the basic salt compound of Al added to the aqueous alkali carbonate solution is 1.0 to 3 in terms of Al with respect to Fe in the aqueous ferrous salt solution. .
It is desirable to be in the range of 0 atomic%.

【0021】次に、本発明方法実施にあたっての諸条件
について述べる。
Next, various conditions for implementing the method of the present invention will be described.

【0022】本発明の紡錘状を呈したゲータイト粒子の
生成反応において使用される第一鉄塩水溶液としては、
硫酸第一鉄水溶液、塩化第一鉄水溶液、硝酸第一鉄水溶
液等を使用することができる。
The ferrous salt aqueous solution used in the production reaction of the spindle-shaped goethite particles of the present invention includes:
An aqueous ferrous sulfate solution, an aqueous ferrous chloride solution, an aqueous ferrous nitrate solution, or the like can be used.

【0023】本発明において使用される炭酸アルカリ水
溶液としては、炭酸ナトリウム水溶液、炭酸カリウム水
溶液、炭酸アンモニウム水溶液等を使用することができ
る。
As the aqueous alkali carbonate solution used in the present invention, an aqueous sodium carbonate solution, an aqueous potassium carbonate solution, an aqueous ammonium carbonate solution and the like can be used.

【0024】本発明において第一鉄塩水溶液中に添加し
て使用されるAlの酸性塩化合物としては、硫酸アルミ
ニウム、塩化アルミニウム、硝酸アルミニウム等を使用
することができる。
As the acidic salt compound of Al used in the present invention by being added to the aqueous ferrous salt solution, aluminum sulfate, aluminum chloride, aluminum nitrate and the like can be used.

【0025】この場合の添加量は、第一鉄塩水溶液中の
Feに対しAl換算で1.0〜3.0原子%の範囲であ
る。1.0原子%未満の場合でもよいが、金属磁性粒子
粉末とし、磁気記録媒体とする際に結合剤樹脂とのなじ
みが不充分となるため、分散性などに問題が生じる。
3.0原子%を越える場合には、得られるゲータイト粒
子が微粒子となり、所期の効果が得られない。
The amount of addition in this case is in the range of 1.0 to 3.0 atomic% in terms of Al with respect to Fe in the aqueous ferrous salt solution. Although it may be less than 1.0 atomic%, when the metal magnetic particle powder is used as the magnetic recording medium, the affinity with the binder resin becomes insufficient, so that problems such as dispersibility arise.
If it exceeds 3.0 atomic%, the obtained goethite particles become fine particles, and the desired effect cannot be obtained.

【0026】本発明において炭酸アルカリ水溶液中に添
加して使用されるAlの塩基性塩化合物としては、アル
ミン酸ナトリウム、アルミン酸カリウム、アルミン酸ア
ンモニウム等を使用することができる。
In the present invention, as the basic salt compound of Al to be used by being added to the aqueous alkali carbonate solution, sodium aluminate, potassium aluminate, ammonium aluminate and the like can be used.

【0027】この場合の添加量は、第一鉄塩水溶液中の
Feに対しAl換算で1.0〜3.0原子%の範囲であ
る。1.0原子%未満の場合でもよいが、金属磁性粒子
粉末とし、磁気記録媒体とする際に結合剤樹脂とのなじ
みが不充分となるため、分散性などに問題が生じる。
3.0原子%を越える場合には、得られるゲータイト粒
子が粗大化するため、所期の効果が得られない。
In this case, the amount of addition is in the range of 1.0 to 3.0 atomic% in terms of Al with respect to Fe in the aqueous ferrous salt solution. Although it may be less than 1.0 atomic%, when the metal magnetic particle powder is used as the magnetic recording medium, the affinity with the binder resin becomes insufficient, so that problems such as dispersibility arise.
If the content exceeds 3.0 atomic%, the desired effect cannot be obtained because the obtained goethite particles are coarse.

【0028】本発明における前記各Al化合物の総和の
添加量は、Feに対しAl換算で1.3原子%以上であ
れば良く、好ましくは2.0〜6.0原子%の範囲であ
る。1.3原子%未満の場合には、金属磁性粒子粉末と
し、磁気記録媒体とする際に結合剤樹脂とのなじみが不
充分となり、分散性などに問題が生じることがあるた
め、2.0原子%以上が好ましい。6.0原子%を越え
て添加しても、6.0原子%を越えて添加した量のAl
化合物は得られるゲータイト粒子に含有されないので意
味がない。
In the present invention, the total addition amount of the respective Al compounds is at least 1.3 atomic% in terms of Al with respect to Fe.
And preferably in the range of 2.0 to 6.0 atomic%.
You. If less than 1.3 atomic%, the metal magnetic particles
However, when used as a magnetic recording medium, it does not
May be sufficient, causing problems in dispersibility, etc.
Therefore, the content is preferably 2.0 atomic% or more. Even if it is added in excess of 6.0 atomic%, the amount of Al added in excess of 6.0 atomic%
The compound is meaningless because it is not contained in the resulting goethite particles.

【0029】また、Alの酸性塩化合物と塩基性塩化合
物との原子比は、1:2〜2:1の範囲である。1:2
未満の場合には、得られるゲータイト粒子が粗大化する
ため、目的の効果が得られない。2:1を越える場合に
は、得られるゲータイト粒子が微粒子となり、所期の効
果が得られない。
The atomic ratio between the acidic salt compound and the basic salt compound of Al is in the range of 1: 2 to 2: 1. 1: 2
If it is less than 1, the obtained goethite particles become coarse, and the desired effect cannot be obtained. If the ratio exceeds 2: 1, the obtained goethite particles become fine particles, and the desired effect cannot be obtained.

【0030】本発明における各Al化合物の添加時期
は、中和してFeCO3 を含む懸濁液とする前のそれぞ
れの第一鉄塩水溶液中或いは炭酸アルカリ水溶液中であ
り、該水溶液中に固形の塩を添加して攪拌・溶解する
か、または、それぞれを別途溶解した水溶液を添加・混
合すればよい。
In the present invention, each Al compound is added in a ferrous salt aqueous solution or an alkali carbonate aqueous solution before neutralization into a suspension containing FeCO 3 . May be added and stirred or dissolved, or an aqueous solution in which each is separately dissolved may be added and mixed.

【0031】尚、Alの酸性塩化合物とAlの塩基性塩
化合物との両化合物を直接混合して中和時に添加した場
合には、Alのコロイドが生成し、各Al化合物を本発
明とは逆の前記各水溶液中に添加した場合にも、また、
Alのコロイドが生成するために所期の効果が得られな
い。
When both the acidic salt compound of Al and the basic salt compound of Al are directly mixed and added at the time of neutralization, an Al colloid is formed, and each Al compound is defined in the present invention. Conversely, when added to each of the aqueous solutions,
The desired effect cannot be obtained due to the formation of Al colloid.

【0032】本発明におけるFeCO3 を含む懸濁液の
pH値は、従来法のそれと同様に8〜10である。pH
8未満の場合又はpHが10を越える場合には、粒度が
均斉な紡錘状を呈したゲータイト粒子が得られない。
The pH value of the suspension containing FeCO 3 in the present invention is 8 to 10 as in the conventional method. pH
If it is less than 8, or if the pH exceeds 10, no spindle-shaped goethite particles having a uniform particle size can be obtained.

【0033】本発明においては、FeCO3 を含む懸濁
液を非酸化性雰囲気下で熟成させることが好ましい。熟
成は、非酸化性雰囲気下の前記懸濁液を、通常、40〜
80℃の温度範囲で行なうのが好適である。40℃未満
の場合には、軸比が小さくなり十分な熟成効果が得られ
難く、80℃を越える場合には、粒状マグネタイトが混
在してくることがある。
In the present invention, the suspension containing FeCO 3 is preferably aged in a non-oxidizing atmosphere. Aging is performed by subjecting the suspension under a non-oxidizing atmosphere to usually 40 to
It is preferable to carry out in a temperature range of 80 ° C. If the temperature is lower than 40 ° C., the axial ratio becomes small and it is difficult to obtain a sufficient aging effect. If the temperature is higher than 80 ° C., particulate magnetite may be mixed.

【0034】また、熟成時間としては、30〜300分
間である。30分間未満の場合には、十分に軸比を大き
くすることができない。300分間を越えてもよいが、
必要以上に長時間とする意味がない。
The aging time is 30 to 300 minutes. If the time is less than 30 minutes, the axial ratio cannot be sufficiently increased. It can be over 300 minutes,
There is no point in taking longer than necessary.

【0035】非酸化性雰囲気とするには、前記懸濁液の
反応容器内に不活性ガス(N2 ガスなど)又は還元性ガ
ス(H2 ガスなど)を通気すればよい。
In order to form a non-oxidizing atmosphere, an inert gas (such as N 2 gas) or a reducing gas (such as H 2 gas) may be passed through the reaction vessel of the suspension.

【0036】本発明における酸化反応時の温度は、通
常、ゲータイト粒子が生成する80℃以下の温度で行え
ばよい。80℃を越える場合には、紡錘状を呈したゲー
タイト粒子中に粒状マグネタイト粒子が混在してくる。
The temperature at the time of the oxidation reaction in the present invention may be usually at a temperature of 80 ° C. or less at which goethite particles are formed. When the temperature exceeds 80 ° C., particulate magnetite particles are mixed in spindle-shaped goethite particles.

【0037】本発明における酸化手段は、常法に従って
酸素含有ガス(例えば空気)を液中に通気することによ
り行い、必要により機械的操作による攪拌を伴ってもよ
い。
The oxidizing means in the present invention is carried out by passing an oxygen-containing gas (for example, air) through the liquid according to a conventional method, and may be accompanied by stirring by mechanical operation if necessary.

【0038】本発明において、加熱還元時の粒子形状の
くずれ及び粒子間の焼結を防止する為に、あらかじめ出
発原料をNi化合物、Al化合物、Si化合物、P化合
物、Co化合物、Mg化合物、B化合物及びZn化合物
から選ばれる金属化合物の1種又は2種以上で被覆処理
を施すことが好ましく、これらの金属化合物は焼結防止
効果を有するだけでなく、還元速度を制御する働きも有
するので、必要に応じて組み合わせて使用することが好
ましい。
In the present invention, in order to prevent the deformation of the particle shape and the sintering between the particles during the heat reduction, the starting materials are made of Ni compound, Al compound, Si compound, P compound, Co compound, Mg compound, B compound in advance. It is preferable to apply a coating treatment with one or more metal compounds selected from compounds and Zn compounds. Since these metal compounds have not only a sintering preventing effect but also a function of controlling a reduction rate, It is preferable to use them in combination as needed.

【0039】上記金属化合物で被覆処理を施した出発原
料は、そのまま還元しても目的とする鉄を主成分とする
金属磁性粒子粉末を得ることができるが、磁気特性、粉
体特性のコントロール及び形状のコントロールの為に
は、常法により、還元に先立って、あらかじめ、非還元
性ガス雰囲気中において加熱処理を施しておくことが好
ましい。
The starting material coated with the above metal compound can be reduced as it is to obtain the desired metal magnetic particle powder containing iron as a main component. In order to control the shape, it is preferable to perform a heat treatment in a non-reducing gas atmosphere in advance before the reduction by a conventional method.

【0040】上記非還元性ガス雰囲気中における加熱処
理は、空気、酸素ガス、窒素ガス流下、300〜800
℃の温度範囲で行うことができ、該加熱処理温度は、出
発原料粒子の被覆処理に用いた金属化合物の種類に応じ
て適宜選択することがより好ましい。800℃を越える
場合には、粒子の変形と粒子及び粒子相互間の焼結を引
き起こしてしまう。
The heat treatment in the non-reducing gas atmosphere is performed under a flow of air, oxygen gas, and nitrogen gas at 300 to 800.
C., and the heat treatment temperature is more preferably selected as appropriate according to the type of the metal compound used for coating the starting material particles. When the temperature exceeds 800 ° C., deformation of the particles and sintering between the particles and the particles are caused.

【0041】本発明における加熱還元の温度範囲は、3
00〜550℃が好ましい。300℃未満である場合に
は、還元反応の進行が遅く、長時間を要する。また、5
50℃を越える場合には、還元反応が急激に進行して粒
子の変形と、粒子及び粒子相互間の焼結を引き起こして
しまう。
The temperature range of the heat reduction in the present invention is 3
00-550 degreeC is preferable. When the temperature is lower than 300 ° C., the progress of the reduction reaction is slow and a long time is required. Also, 5
If the temperature exceeds 50 ° C., the reduction reaction proceeds rapidly, causing deformation of the particles and sintering between the particles.

【0042】本発明における加熱還元後の鉄を主成分と
する金属磁性粒子粉末は周知の方法、例えば、トルエン
等の有機溶剤中に浸漬する方法及び還元後の鉄を主成分
とする金属磁性粒子粉末の雰囲気を一旦不活性ガスに置
換した後、不活性ガス中の酸素含有量を徐々に増加させ
ながら最終的に空気とすることによって徐酸化する方法
等により空気中に取り出すことができる。
The iron-based metal magnetic particles powder after heat reduction in the present invention can be prepared by a known method, for example, immersion in an organic solvent such as toluene, or reduced iron-based metal magnetic particles. After the atmosphere of the powder is once replaced with an inert gas, it can be taken out into the air by a method such as gradually oxidizing by gradually increasing the oxygen content in the inert gas into air while gradually increasing the oxygen content.

【0043】本発明においては、従来から鉄を主成分と
する金属磁性粒子粉末の各種特性の向上の為に、出発原
料であるゲータイト粒子の生成に際し、Al化合物と共
に通常添加されるCo化合物、Ni化合物、Cr化合
物、Zn化合物、Mn化合物、P化合物、Si化合物、
B化合物から選ばれた1種又は2種以上とを添加するこ
とができ、この場合にも、本発明の目的とする粒度が均
斉であって、樹枝状粒子が混在しておらず、しかも、高
い保磁力を有する紡錘状を呈したゲータイト粒子粉末を
得ることができる。
In the present invention, in order to improve the various characteristics of the metal magnetic particle powder containing iron as a main component, a Co compound, a Ni compound usually added together with an Al compound when producing goethite particles as a starting material have been conventionally used. Compound, Cr compound, Zn compound, Mn compound, P compound, Si compound,
One or two or more compounds selected from the B compounds can be added, and also in this case, the target particle size of the present invention is uniform, dendritic particles are not mixed, and Spindle-shaped goethite particles having high coercive force can be obtained.

【0044】[0044]

【作用】前述した通りの構成を採る本発明の作用は次の
通りである。
The operation of the present invention having the above-described configuration is as follows.

【0045】粒度が均斉であって樹枝状粒子が混在して
おらず、しかも、高い保磁力を有する金属磁性粒子粉末
を得ようとする場合においては、前出の方法による場
合には、軸比の大きな針状ゲータイト粒子は生成する
が、樹枝状粒子が混在しており、均斉な粒度とは言い難
いものであるため、本発明者は、前出の方法による粒
度が均斉であって樹枝状粒子が混在していない紡錘状を
呈したゲータイト粒子を改善することにより、粒度が均
斉であって樹枝状粒子が混在しておらず、しかも、高い
保磁力を有する金属磁性粒子粉末を得ることに取り組ん
だ。
In order to obtain metal magnetic particle powder having a uniform particle size, no dendritic particles, and a high coercive force, the axial ratio is determined by the above method. Although large needle-like goethite particles are generated, dendritic particles are mixed, and it is difficult to say that the particles have a uniform particle size. By improving spindle-shaped goethite particles in which particles are not mixed, it is possible to obtain metal magnetic particle powder having a uniform particle size, no dendritic particles mixed, and high coercive force. Worked.

【0046】一方、金属磁性粒子粉末にAl化合物を用
いることによって、磁気記録媒体とする際の分散性、充
填性、テープ表面の平滑性の向上することができること
が知られている。尚、磁性粒子粉末としては結合剤樹脂
とのなじみにより評価され、その評価法としては後述す
る固体の酸量・塩基量により測定できる。一般に現在多
く用いられている結合剤樹脂(例えば、塩化ビニル酢酸
ビニル共重合体にポリウレタン樹脂を加える。)に対し
ては固体塩基量が多いほど結合剤樹脂とのなじみがよい
とされている。
On the other hand, it is known that the use of an Al compound in the metal magnetic particle powder can improve the dispersibility, filling property, and smoothness of the tape surface when used as a magnetic recording medium. The magnetic particle powder is evaluated based on the familiarity with the binder resin, and the evaluation method can be measured by the solid acid amount and base amount described later. In general, it is said that the larger the amount of the solid base, the better the compatibility with the binder resin which is generally used at present (for example, a polyurethane resin is added to a vinyl chloride-vinyl acetate copolymer).

【0047】金属磁性粒子粉末にAl化合物を用いる方
法においても、(A)ゲータイト粒子の生成反応時に添
加する方法(例えば、前掲特公平3−43324号公
報)、(B)加熱処理前のゲータイト粒子または該ゲー
タイト粒子を加熱脱水した後のヘマタイト粒子の粒子表
面にAl化合物を被覆する方法(例えば、特開昭52−
134858号公報)及び(C)得られた金属磁性粒子
粉末の粒子表面にAl化合物を被覆する方法(例えば、
特開昭58−161709号公報)等がある。
In the method of using an Al compound in the metal magnetic particle powder, (A) a method of adding at the time of a reaction for forming goethite particles (for example, Japanese Patent Publication No. 3-43324, cited above), and (B) a goethite particle before heat treatment Alternatively, a method of coating the surface of the hematite particles after heating and dehydrating the goethite particles with an Al compound (see, for example,
No. 134858) and (C) a method of coating the particle surface of the obtained metal magnetic particle powder with an Al compound (for example,
JP-A-58-161709).

【0048】しかしながら、(B)の方法については、
磁気特性、殊に保磁力が低下する。(C)の方法につい
ては、金属磁性粒子粉末の湿式粉砕・解膠等を必要とす
るため工業的とは言えない。また、(A)の方法につい
ては、前述の通り、高い保磁力を得ることは困難であ
る。
However, regarding the method (B),
The magnetic properties, especially the coercive force, decrease. The method (C) is not industrial because it requires wet pulverization and peptization of the magnetic metal particles. In the method (A), as described above, it is difficult to obtain a high coercive force.

【0049】しかし、本発明者が種々検討した結果、
(A)の方法においては、ゲータイト粒子の生成過程に
おけるAl化合物の添加時期によって特性が異なること
がわかった。添加時期としては、(a)中和してFeC
O3 を含む懸濁液とする前の各原料水溶液に添加する方
法、(b)前記懸濁液の生成後に添加する方法、(c)
FeCO3 を含む懸濁液を熟成中または熟成後に添加す
る方法、(d)熟成後の酸化反応途中に添加する方法及
び(e)酸化反応終了後に添加する方法等がある。
However, as a result of various studies by the present inventors,
In the method of (A), it was found that the characteristics were different depending on the timing of adding the Al compound in the process of forming goethite particles. The addition timing is as follows: (a) neutralization and FeC
A method of adding to each raw material aqueous solution before forming a suspension containing O 3 , (b) a method of adding after the formation of the suspension, (c)
There are a method of adding a suspension containing FeCO 3 during or after ripening, a method (d) of adding during the oxidation reaction after aging, and a method (e) of adding after the oxidation reaction.

【0050】そのうち、(b)及び(c)の時期に添加
した場合には、生成するゲータイト粒子が超微細化する
ため非常に扱い難く保磁力も低いものとなる。(d)の
時期に添加した場合には、粒子が粗大化する共に軸比が
十分ではなく、(e)の時期に添加した場合には、前述
の(B)の方法と同様の結果であった。
Of these, when added at the times of (b) and (c), the resulting goethite particles become extremely fine, so that they are very difficult to handle and have low coercive force. When added at the time of (d), the particles become coarse and the axial ratio is not sufficient, and when added at the time of (e), the result is the same as that of the method (B) described above. Was.

【0051】(a)の時期に添加した場合においては、
前述した通り、添加する水溶性Al化合物、殊に、アル
ミナゾルの場合には、ゲータイト粒子が微細かつ軸比の
著しく小さいものしか得られず、アルミン酸ソーダの場
合には、粒子が粗大化すると共に軸比の大きなものは得
られ難く、塩化アルミニウムや硫酸アルミニウムの場合
には、軸比の大きなものが得られ難い等の問題がそれぞ
れあることが分かった。
When added at the time of (a),
As described above, in the case of a water-soluble Al compound to be added, particularly, in the case of alumina sol, only goethite particles having a fine and extremely small axial ratio are obtained, and in the case of sodium aluminate, the particles are coarsened. It was found that those having a large axial ratio were difficult to obtain, and in the case of aluminum chloride and aluminum sulfate, there were problems that it was difficult to obtain a large axial ratio.

【0052】この理由について、本発明者は、アルミナ
ゾルの場合には、アルミナゾルが固体であり、中和時に
添加すると生成するゲータイト粒子の核晶となって微細
かつ軸比の著しく小さいものしか得られない。また、ア
ルミニウムには凝集剤としての働きと結晶成長制御剤と
しての働きがあり、Alの酸性塩化合物を単独で使用し
た際には結晶成長制御効果のみが発揮されて軸比の大き
なものが得られず、Alの塩基性塩化合物を単独で使用
した際には凝集効果のみが発揮されて粒子が粗大化する
のではないかと考えている。この理由については未だ明
らかではないが、アルミニウムが中和されて固体とな
り、鉄中和物に吸着した際の吸着の仕方とアルミニウム
化合物そのものの構造に起因しているのではないか考え
ている。
For this reason, the present inventors have found that in the case of alumina sol, the alumina sol is a solid, and when added at the time of neutralization, it becomes a nucleus of goethite particles to be formed, and only fine particles having a very small axial ratio can be obtained. Absent. Further, aluminum has both a function as a coagulant and a function as a crystal growth controlling agent. When an acid salt of Al is used alone, only an effect of controlling crystal growth is exerted, and a material having a large axial ratio is obtained. However, it is considered that when the basic salt compound of Al is used alone, only the aggregation effect is exerted and the particles are coarsened. Although the reason for this is not yet clear, it is believed that the aluminum is neutralized to form a solid, which is attributed to the manner of adsorption when adsorbed to the neutralized iron and the structure of the aluminum compound itself.

【0053】そこで、本発明者は、金属磁性粒子粉末と
した場合に結合剤樹脂とのなじみを向上させることがで
きるAl化合物を多く含有した紡錘状を呈したゲータイ
ト粒子が得られるかを種々検討した結果、第一鉄塩水溶
液と炭酸アルカリ水溶液とを中和してFeCO3 を含む
懸濁液とする前に、それぞれ、前記第一鉄塩水溶液中に
はAlの酸性塩化合物を添加しておき、更に、前記炭酸
アルカリ水溶液中にはAlの塩基性塩化合物を添加して
から中和反応を行うことによりFeCO3 を含む懸濁液
とし、次いで、酸素含有ガスを通気して酸化反応を行う
ことにより、粒度が均斉であって樹枝状粒子が混在して
おらず、しかも、多くのAlを含有する紡錘状を呈した
ゲータイト粒子を生成することができることが見出した
のである。
Therefore, the present inventor studied variously whether spindle-shaped goethite particles containing a large amount of an Al compound, which can improve the compatibility with the binder resin, can be obtained when the metal magnetic particles are used as the powder. As a result, before neutralizing the aqueous ferrous salt solution and the aqueous alkali carbonate solution into a suspension containing FeCO 3 , an acidic salt compound of Al was added to the aqueous ferrous salt solution, respectively. Further, a basic salt compound of Al is added to the aqueous alkali carbonate solution and then a neutralization reaction is performed to form a suspension containing FeCO 3 , and then an oxygen-containing gas is passed to perform an oxidation reaction. It has been found that by performing this, it is possible to produce spindle-shaped goethite particles having a uniform particle size, no dendritic particles being mixed, and having a large amount of Al.

【0054】この理由としては、Alの酸性塩化合物は
同じ酸性である第一鉄塩水溶液に添加し、Alの塩基性
塩化合物は同じアルカリ性である炭酸アルカリ水溶液に
添加することにより、中和反応がスムーズに行われる中
で各Al化合物がFeCO3中に取り込まれ、更に、紡
錘状のゲータイト粒子を生成する過程においてうまく多
くのAl化合物を含有させることができたものと考えて
おり、それは、前述の凝集効果と結晶成長制御効果が形
状制御に有利に働いたためと考えている。
The reason for this is that the acid salt compound of Al is added to an aqueous solution of ferrous salt having the same acidity, and the basic salt compound of Al is added to an aqueous solution of alkali carbonate having the same alkalinity. Is carried out smoothly, each Al compound is taken into FeCO 3 , and further, it is thought that in the process of forming spindle-shaped goethite particles, a large amount of Al compounds could be successfully contained. It is considered that the agglomeration effect and the crystal growth control effect described above advantageously acted on shape control.

【0055】その結果、前記紡錘状を呈したゲータイト
粒子又は前記ゲータイト粒子を加熱脱水して得られた紡
錘状を呈したヘマタイト粒子を還元性ガス中で加熱還元
することにより、粒度が均斉であって樹枝状粒子が混在
しておらず、しかも、高い保磁力を有する紡錘状を呈し
た鉄を主成分とする金属磁性粒子粉末が得られたのであ
る。
As a result, the spindle-shaped goethite particles or the spindle-shaped hematite particles obtained by heating and dehydrating the goethite particles are heated and reduced in a reducing gas, so that the particle sizes are uniform. As a result, a spindle-shaped iron-based metal magnetic particle powder containing no dendritic particles and having a high coercive force was obtained.

【0056】[0056]

【実施例】次に、実施例並びに比較例により、本発明を
説明する。尚、以下の実施例並びに比較例における粒子
の平均径、軸比は、いずれも電子顕微鏡写真から測定し
た数値の平均値を示した。
Next, the present invention will be described with reference to examples and comparative examples. In the following Examples and Comparative Examples, the average diameter and the axial ratio of the particles were all the average values of the values measured from the electron micrographs.

【0057】鉄を主成分とする金属磁性粒子粉末の磁気
特性及び塗膜特性は、「振動試料磁力計VSM−3S−
15」(東英工業(株)製)を使用し、外部磁場10K
Oeまでかけて測定した。
The magnetic properties and coating properties of the metal magnetic particles containing iron as a main component are described in "Vibration sample magnetometer VSM-3S-
15 "(manufactured by Toei Industry Co., Ltd.) and an external magnetic field of 10K
It was measured over Oe.

【0058】鉄を主成分とする金属磁性粒子粉末の結合
剤樹脂とのなじみについては、磁性粉にn−ブチルアミ
ン(塩基性物質)を吸着させ、吸着しなかったn−ブチ
ルアミンの濃度を0.1NのHClO4 /酢酸溶液で滴
定して測定した固体酸量または磁性粉にミリスチン酸
(酸性物質)を吸着させ、吸着しなかったミリスチン酸
の濃度を「イオンクロマトグラフHIC−6A」(島津
製作所製)により測定した固体塩基量により求めた。
Regarding the compatibility of the metal magnetic particle powder containing iron as a main component with the binder resin, n-butylamine (basic substance) is adsorbed on the magnetic powder, and the concentration of the non-adsorbed n-butylamine is adjusted to 0.1. The amount of solid acid measured by titration with a 1N HClO 4 / acetic acid solution or the amount of myristic acid (acidic substance) adsorbed on magnetic powder and the concentration of myristic acid not adsorbed are measured by “ion chromatography HIC-6A” (Shimadzu Corporation) From the amount of the solid base measured by the method described in (1).

【0059】<紡錘状を呈したゲータイト粒子粉末の製
造> 実施例1〜3、比較例1〜5;
<Production of Spindle-Shaped Goethite Particle Powder> Examples 1 to 3 and Comparative Examples 1 to 5;

【0060】実施例1 毎分50lの割合でN2 ガスを流すことによって非酸化
性雰囲気に保持された反応容器中に、硫酸アルミニウム
51.3g(硫酸第一鉄水溶液中のFe2+に対し1.5
原子%に該当する。)を溶解させたFe2+0.8mol
/lを含む硫酸第一鉄水溶液25lとアルミン酸ナトリ
ウム24.6g(硫酸第一鉄水溶液中のFe2+に対し
1.5原子%に該当する。)を溶解させた1.6mol
/lのNa2 CO3 水溶液25l(硫酸第一鉄水溶液中
のFe2+に対し2.0当量に該当する。)とを混合し、
pH9.4、温度56℃においてFeCO3 を含む懸濁
液の生成した。
Example 1 In a reaction vessel maintained in a non-oxidizing atmosphere by flowing N 2 gas at a rate of 50 l / min, 51.3 g of aluminum sulfate (relative to Fe 2+ in an aqueous ferrous sulfate solution) was added. 1.5
It corresponds to atomic%. ) Dissolved Fe 2+ 0.8mol
/ L and 1.6 mol of 24.6 g of sodium aluminate (corresponding to 1.5 atomic% based on Fe 2+ in the aqueous ferrous sulfate solution).
/ L of an aqueous solution of Na 2 CO 3 (corresponding to 2.0 equivalents to Fe 2+ in an aqueous solution of ferrous sulfate).
A suspension containing FeCO 3 was formed at a pH of 9.4 and a temperature of 56 ° C.

【0061】上記懸濁液中に、引き続き、毎分50lの
N2 ガスを流しながら、温度56℃において2時間保持
して熟成した後、N2 ガスを止めて、当該懸濁液の温度
を55℃とし、毎分150lの空気を当該懸濁液中に4
時間通気して黄褐色沈澱粒子を生成させた。黄色褐色沈
澱粒子は、常法により、濾別、水洗、乾燥、粉砕した。
After continuously ripening the suspension at a temperature of 56 ° C. for 2 hours while flowing 50 l of N 2 gas per minute, the N 2 gas was stopped and the temperature of the suspension was lowered. 55 ° C. and 150 liters of air per minute into the suspension
Vent for a period of time to produce tan precipitated particles. The yellow-brown precipitate particles were separated by filtration, washed with water, dried and pulverized by a conventional method.

【0062】得られた黄褐色粒子粉末は、X線回折の結
果、ゲータイトであり、図1に示す電子顕微鏡写真(×
30000)から明らかな通り、Al化合物はAl換算
で0.76wt%含有する平均値で長軸径0.19μ
m、軸比10の紡錘状を呈した粒子からなり、粒度が均
斉で樹枝状粒子が混在しないものであった。
As a result of X-ray diffraction, the obtained tan particle powder was goethite.
As is clear from (30000), the Al compound contained 0.76 wt% in terms of Al and had a major axis diameter of 0.19 μm as an average value.
The particles consisted of spindle-shaped particles having a m and an axial ratio of 10 and had uniform particle sizes and did not contain dendritic particles.

【0063】実施例2及び3、比較例1〜5 ゲータイト粒子の生成における第一鉄塩水溶液の種類、
炭酸アルカリ水溶液の種類、第一鉄塩水溶液中又は炭酸
アルカリ水溶液中に添加・溶解させたAlの酸性塩化合
物又はAlの塩基性塩化合物の種類及びFe2+に対する
使用量、前記各Alの化合物の添加溶液及び時期、熟成
工程の通気ガス流量、温度及び時間並びに反応温度を種
々変化させた以外は実施例1と同様にして紡錘状を呈し
たゲータイト粒子粉末を得た。
Examples 2 and 3, Comparative Examples 1 to 5 Types of ferrous salt aqueous solution in producing goethite particles,
Kind of alkali carbonate aqueous solution, kind of Al acidic salt compound or Al basic salt compound added / dissolved in ferrous salt aqueous solution or alkali carbonate aqueous solution and amount used for Fe 2+ , Compound of each of the above Al Goitite particles having a spindle shape were obtained in the same manner as in Example 1 except that the addition solution and the timing of, the flow rate of the aerated gas in the aging step, the temperature and the time, and the reaction temperature were variously changed.

【0064】この時の主要製造条件及びゲータイト粒子
粉末の諸特性を表1及び表2に示す。尚、比較例2にお
いては、図5に示す電子顕微鏡写真(×30000)か
ら明らかな通り、微細な不定形粒子であったので長軸径
と軸比の測定は割愛した。
Tables 1 and 2 show the main production conditions and various properties of the goethite particles at this time. In Comparative Example 2, as is clear from the electron micrograph (× 30000) shown in FIG. 5, the measurement of the major axis diameter and the axial ratio was omitted because the particles were fine irregular particles.

【0065】[0065]

【表1】 [Table 1]

【0066】[0066]

【表2】 [Table 2]

【0067】<紡錘状を呈したヘマタイト粒子粉末の製
造> 実施例4〜6、比較例6〜9;
<Production of Spindle-Shaped Hematite Particle Powder> Examples 4 to 6, Comparative Examples 6 to 9;

【0068】実施例4 実施例1で得られた濾別、水洗した後の紡錘状を呈した
ゲータイト粒子1500gに相当量のプレスケーキを4
0lの水中に懸濁させた。この時の懸濁液のpHは8.
9であった。次いで、上記懸濁液に酢酸コバルト315
g(ゲータイトに対し酢酸コバルトとして21wt%に
該当する。)を溶解した水溶液1lを添加して10分間
攪拌・分散した、次いで、上記懸濁液にホウ酸180g
(ゲータイトに対しホウ酸として12wt%に該当す
る。)を添加し、10分間攪拌した。次いで、該懸濁液
のpHが7.3となるように15%濃度のアンモニア水
溶液を添加した後、濾別して不要な塩を除去した。該濾
別したゲータイトプレスケーキを乾燥し、Co化合物と
B化合物で被覆されたゲータイト粒子を得た。得られた
ゲータイト中のCoとB含有量はそれぞれCo化合物は
Co換算で3.7原子%、B化合物はB換算で0.71
原子%であった。
Example 4 A considerable amount of press cake was added to 1500 g of spindle-shaped goethite particles obtained in Example 1 after filtration and washing with water.
Suspended in 0 l of water. The pH of the suspension at this time was 8.
Nine. Then, 315 of cobalt acetate was added to the above suspension.
g (corresponding to 21 wt% of cobalt acetate with respect to goethite) was added, and the mixture was stirred and dispersed for 10 minutes. Then, 180 g of boric acid was added to the suspension.
(Corresponding to 12 wt% of boric acid with respect to goethite) and stirred for 10 minutes. Next, an aqueous ammonia solution having a concentration of 15% was added so that the pH of the suspension became 7.3, and the resulting mixture was separated by filtration to remove unnecessary salts. The goethite press cake separated by filtration was dried to obtain goethite particles coated with a Co compound and a B compound. The content of Co and B in the obtained goethite was 3.7 atomic% in terms of Co for the Co compound, and 0.71% in terms of B for the B compound.
Atomic%.

【0069】次いで、上記ゲータイト粒子を空気中40
0℃で30分間加熱脱水して紡錘状を呈したヘマタイト
粒子を得た。
Next, the goethite particles were placed in air for 40 minutes.
After heating and dehydration at 0 ° C. for 30 minutes, spindle-shaped hematite particles were obtained.

【0070】実施例5及び6、比較例6〜9 被処理粒子の種類を変えた以外は、実施例4と同様にし
て紡錘状を呈したヘマタイト粒子を得た。この時の主要
な製造条件及び諸特性を表3に示す。尚、比較例6にお
いては、Co化合物とB化合物に加え、更にAl化合物
(ゲータイトに対し硝酸アルミニウムとして20wt%
に該当する。)を被覆した。
Examples 5 and 6, Comparative Examples 6 to 9 Spindle-shaped hematite particles were obtained in the same manner as in Example 4, except that the type of particles to be treated was changed. Table 3 shows the main production conditions and various characteristics at this time. In Comparative Example 6, in addition to the Co compound and the B compound, an Al compound (20 wt% as aluminum nitrate with respect to goethite) was used.
Corresponds to. ) Was coated.

【0071】[0071]

【表3】 [Table 3]

【0072】<紡錘状を呈した鉄を主成分とする金属磁
性粒子粉末の製造> 実施例7〜9、比較例10〜13;
<Production of spindle-shaped iron-based metal magnetic particle powder> Examples 7 to 9, Comparative Examples 10 to 13;

【0073】実施例7 実施例4で得られた紡錘状を呈したヘマタイト粒子粉末
100gを約10lの容積の回転レトルト還元容器に投
入し、駆動回転させながらH2 ガスを毎分20lの割合
で通気し、還元温度400℃で還元した。
Example 7 100 g of the spindle-shaped hematite particle powder obtained in Example 4 was charged into a rotary retort reduction vessel having a volume of about 10 l, and H 2 gas was supplied at a rate of 20 l / min while being driven to rotate. It was aerated and reduced at a reduction temperature of 400 ° C.

【0074】還元して得られた紡錘状を呈した鉄を主成
分とする金属磁性粒子粉末は、空気中に取り出した時急
激な酸化を起こさないように、トルエン液中に浸漬して
取り出した。一部を取り出し、トルエンを蒸発させなが
ら表面に安定な酸化被膜を形成した。
The spindle-shaped iron-based metal magnetic particle powder obtained by reduction is immersed in a toluene solution and taken out so as not to cause rapid oxidation when taken out into the air. . A part was taken out and a stable oxide film was formed on the surface while evaporating toluene.

【0075】この紡錘状を呈した鉄を主成分とする金属
磁性粒子粉末は、電子顕微鏡観察の結果、平均長軸0.
13μm、軸比7.5であり、粒度が均斉で樹枝状粒子
の少ないものであった。また、Al化合物はFeに対し
Al換算で1.10wt%であり、磁気特性は、保磁力
Hc1655Oe、飽和磁化σs149emu/gであ
った。また、固体酸量は0.235mg/m2 であり、
固体塩基量は0.858mg/m2 であった。
As a result of observation with an electron microscope, this spindle-shaped iron-based metal magnetic particle powder was found to have an average major axis of 0.1 mm.
The particle size was 13 μm, the axial ratio was 7.5, the particle size was uniform, and there were few dendritic particles. The Al compound was 1.10 wt% in terms of Al with respect to Fe, and the magnetic properties were a coercive force Hc1655Oe and a saturation magnetization ss149 emu / g. The amount of solid acid is 0.235 mg / m 2 ,
The solid base amount was 0.858 mg / m 2 .

【0076】実施例8及び9、比較例10〜13 被処理粒子の種類並びに還元温度を種々変化させた以外
は実施例7と同様にして紡錘状を呈した鉄を主成分とす
る金属磁性粒子粉末を得た。この時の主要製造条件及び
諸特性を表4に示す。
Examples 8 and 9 and Comparative Examples 10 to 13 Spindle-shaped iron-based metal magnetic particles mainly composed of iron in the same manner as in Example 7 except that the kind of particles to be treated and the reduction temperature were variously changed. A powder was obtained. Table 4 shows the main manufacturing conditions and various characteristics at this time.

【0077】[0077]

【表4】 [Table 4]

【0078】[0078]

【発明の効果】本発明に係る紡錘状を呈した鉄を主成分
とする金属磁性粒子粉末の製造法によれば、前出実施例
に示した通り、粒度が均斉であって樹枝状粒子が混在し
ておらず、しかも、高い保磁力を有する紡錘状を呈した
鉄を主成分とする金属磁性粒子粉末を得ることが出来る
ので、高記録密度、高感度、高出力用磁性粒子粉末とし
て好適である。
According to the method for producing spindle-shaped iron-based metal magnetic particles according to the present invention, as shown in the preceding embodiment, the particle size is uniform and dendritic particles are formed. Suitable for high recording density, high sensitivity, and high output magnetic particle powder, because it is possible to obtain a spindle-shaped iron-based metal magnetic particle powder having a high coercive force without being mixed. It is.

【図面の簡単な説明】[Brief description of the drawings]

【図1】実施例1で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 1 is an electron micrograph (× 3000) showing the particle structure of the spindle-shaped goethite particle powder obtained in Example 1.
0).

【図2】実施例2で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 2 is an electron micrograph (× 3000) showing the particle structure of spindle-shaped goethite particles obtained in Example 2.
0).

【図3】実施例3で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 3 is an electron micrograph (× 3000) showing the particle structure of spindle-shaped goethite particles obtained in Example 3.
0).

【図4】比較例1で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 4 is an electron micrograph (× 3000) showing the particle structure of the spindle-shaped goethite particles obtained in Comparative Example 1.
0).

【図5】比較例2で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 5 is an electron micrograph (× 3000) showing the particle structure of the spindle-shaped goethite particles obtained in Comparative Example 2.
0).

【図6】比較例3で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 6 is an electron micrograph (× 3000) showing the particle structure of the spindle-shaped goethite particles obtained in Comparative Example 3.
0).

【図7】比較例4で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 7 is an electron micrograph (× 3000) showing the particle structure of the spindle-shaped goethite particle powder obtained in Comparative Example 4.
0).

【図8】比較例5で得られた紡錘状を呈したゲータイト
粒子粉末の粒子構造を示す電子顕微鏡写真(×3000
0)である。
FIG. 8 is an electron micrograph (× 3000) showing the particle structure of the spindle-shaped goethite particles obtained in Comparative Example 5.
0).

Claims (2)

(57)【特許請求の範囲】(57) [Claims] 【請求項1】 第一鉄塩水溶液と炭酸アルカリ水溶液と
を反応して得られたFeCO3 を含む懸濁液に酸素含有
ガスを通気して酸化反応を行うことにより紡錘状を呈し
たゲータイト粒子を生成させ、該ゲータイト粒子又は該
ゲータイト粒子を加熱脱水して得られた紡錘状を呈した
ヘマタイト粒子を還元性ガス中で加熱還元する紡錘状を
呈した鉄を主成分とする金属磁性粒子粉末の製造法にお
いて、 あらかじめ、前記第一鉄塩水溶液中にはAlの酸性塩化
合物を、前記炭酸アルカリ水溶液中にはAlの塩基性塩
化合物を、それぞれ添加しておくことを特徴とする紡錘
状を呈した鉄を主成分とする金属磁性粒子粉末の製造
法。
1. A goethite particles exhibited fusiform by performing an oxidation reaction by bubbling an oxygen-containing gas into the suspension containing FeCO 3 obtained by reacting a ferrous salt aqueous solution and aqueous alkali carbonate solution To produce the spindle-shaped iron-based metal magnetic particle powder obtained by heating and reducing the goethite particles or the spindle-shaped hematite particles obtained by heating and dehydrating the goethite particles in a reducing gas. The method of producing a spindle-shaped fiber, wherein an acidic salt compound of Al is added in advance to the aqueous solution of ferrous salt, and a basic salt compound of Al is added to the aqueous solution of alkali carbonate. Of producing metal magnetic particle powder containing iron as a main component and exhibiting the following.
【請求項2】 第一鉄塩水溶液中に添加するAlの酸性
塩化合物が該第一鉄塩水溶液中のFeに対しAl換算で
1.0〜3.0原子%の範囲であり、炭酸アルカリ水溶
液中に添加するAlの塩基性塩化合物が前記第一鉄塩水
溶液中のFeに対しAl換算で1.0〜3.0原子%の
範囲である請求項1記載の紡錘状を呈した鉄を主成分と
する金属磁性粒子粉末の製造法。
2. The method according to claim 1, wherein the acidic salt compound of Al added to the aqueous ferrous salt solution is in the range of 1.0 to 3.0 at% in terms of Al with respect to Fe in the aqueous ferrous salt solution. 2. The spindle-shaped iron according to claim 1, wherein the basic salt compound of Al added to the aqueous solution is in a range of 1.0 to 3.0 atomic% in terms of Al with respect to Fe in the aqueous ferrous salt solution. 3. A method for producing metal magnetic particle powder comprising as a main component.
JP05042118A 1993-02-05 1993-02-05 Method for producing spindle-shaped iron-based metal magnetic particle powder Expired - Fee Related JP3141907B2 (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
JP05042118A JP3141907B2 (en) 1993-02-05 1993-02-05 Method for producing spindle-shaped iron-based metal magnetic particle powder

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
JP05042118A JP3141907B2 (en) 1993-02-05 1993-02-05 Method for producing spindle-shaped iron-based metal magnetic particle powder

Publications (2)

Publication Number Publication Date
JPH06228614A JPH06228614A (en) 1994-08-16
JP3141907B2 true JP3141907B2 (en) 2001-03-07

Family

ID=12627042

Family Applications (1)

Application Number Title Priority Date Filing Date
JP05042118A Expired - Fee Related JP3141907B2 (en) 1993-02-05 1993-02-05 Method for producing spindle-shaped iron-based metal magnetic particle powder

Country Status (1)

Country Link
JP (1) JP3141907B2 (en)

Also Published As

Publication number Publication date
JPH06228614A (en) 1994-08-16

Similar Documents

Publication Publication Date Title
JPH09295814A (en) Spindle-shaped goethite particle powder and method for producing the same, spindle-shaped metallic magnetic particle powder containing iron as a main component and obtained from the goethite particle powder as a starting material, and method for producing the same
JP3750414B2 (en) Spindle-shaped goethite particle powder, spindle-shaped hematite particle powder, spindle-shaped metal magnetic particle powder containing iron as a main component, and production method thereof
JP3412676B2 (en) Spindle-shaped goethite particle powder and method for producing the same
JP3144683B2 (en) Spindle-shaped iron-based metal magnetic particle powder
JP3337046B2 (en) Spindle-shaped metal magnetic particles containing cobalt and iron as main components and method for producing the same
JP3264374B2 (en) Method for producing spindle-shaped iron-based metal magnetic particle powder
JP2852460B2 (en) Method for producing spindle-shaped iron-based metal magnetic particle powder
JPS6411577B2 (en)
JP4378763B2 (en) Method for producing compound particle powder containing iron as its main component
JP3092649B2 (en) Method for producing spindle-shaped metal magnetic particles containing iron as a main component
JP3303896B2 (en) Spindle-shaped iron-based metal magnetic particle powder and method for producing the same
JP3087808B2 (en) Manufacturing method of magnetic particle powder for magnetic recording
JP3171223B2 (en) Method for producing acicular magnetic particle powder
JP2704537B2 (en) Method for producing spindle-shaped goethite particles
JP2965606B2 (en) Method for producing metal magnetic powder
JP2925561B2 (en) Spindle-shaped magnetic iron oxide particles
CN101113506B (en) Magnetic powder suitable for low-noise media
JPH11130439A (en) Spindle-shaped goethite particle powder and method for producing the same, spindle-shaped hematite particle powder and method for producing the same, and spindle-shaped metal magnetic particle powder containing iron as a main component and method for producing the same
JP2743000B2 (en) Spindle-shaped goethite particles and method for producing the same
JP2852459B2 (en) Method for producing spindle-shaped iron-based metal magnetic particle powder
JPH0755827B2 (en) Manufacturing method of spindle-shaped iron-based metallic magnetic particle powder
JPH06228614A (en) Manufacturing method of metallic magnetic particle powder mainly composed of iron and having a spindle shape
JP3003777B2 (en) Method for producing spindle-shaped magnetic iron oxide particles
JPS648042B2 (en)
JPH08165117A (en) Spindle-shaped goethite particle powder containing cobalt and method for producing the same

Legal Events

Date Code Title Description
LAPS Cancellation because of no payment of annual fees